Social Science Education Critical Model according to Jurgen Habermas (Critical Theory) - Racha Suheib Achmad (Penerbit Hellow Pustaka, 2025)
Social science is a branch of science that studies the relationship between humans and their environment, society, and the interactions within it. Understanding the relationship between humans and the social sciences is necessary to achieve a better standard of living. Because humans play an important role in the development of social sciences. The purpose of social sciences is to explain the phenomena of both cooperation and conflict that exist in society. In this case, a structural approach is taken in considering and classifying the various domains involved in the social sciences. Social forces that play a role in the development of social theory. In the history of its development, social sciences are described as how the emergence of social change in Europe in the form of the industrial revolution in England and the social revolution in France in the 19th and 20th centuries accelerated the emergence of social sciences. . explains what the Industrial Revolution was not a single event but a series of interrelated developments that led to the transformation of the Western world from an agricultural to an industrial system. Many people left agriculture for industrial jobs provided by growing factories.